Jago Mentor Solusi Pembelajaran Jarak Jauh Pada Masa Pandemi Covid-19 - Khoirun Nisa Nurul Fitri (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2022)
The Covid-19 pandemic caused chaos, especially in the field of education, schools were closed, teaching and learning activities in schools were disrupted, learning that was initially carried out face-to-face was temporarily unable to be carried out. To overcome these problems, it is necessary to change the design of the model in teaching and learning activities to avoid face-to-face learning. Jago Mentor is an acronym for Learning with Google Classroom, Google Meet, and evaluation with Auto Proctor. Learning in the 12th grade Network System Administration subject is conducted online using Google Classroom where the teacher uploads assignments and materials in the form of modules as well as learning videos and practical tutorial videos. Then the teacher reflects and controls with students on the material and assignments that have been given through Google Classroom through virtual face-to-face meetings using Google Meet. In the evaluation process, the teacher uses the Google Form application that helps Auto Proctor. The use of Auto Proctor can assist teachers in supervising students while working on evaluation questions, although not directly. The application of Jago Mentor makes students more disciplined in participating in online learning and students are more serious, honest, and responsible in carrying out the evaluation process.